Quality Assurance Review Among Independent CPAs: Basis for Improvement Plan - Reyes, Jonathan Delos (International Journal of Research in Interdisciplinary Studies, 2025)
This study investigates the effectiveness of the Quality Assurance Review (QAR) among independent Certified Public Accountants (CPAs) in Laguna Province, Philippines, and its relationship with audit quality. The implementation of QAR is mandated under the Philippine Accountancy Act of 2004, yet micro and small CPA practitioners continue to face significant challenges. This research aimed to identify these barriers and assess how QAR impacts audit practices, to propose an improvement plan. Using a descriptive correlational research design, data were collected from CPAs through a questionnaire. The results revealed that QAR was perceived as generally effective. Audit quality was rated highly in terms of compliance with standards, client confidence, use of technology, and timeliness. A significant relationship was found between the effectiveness of QAR and audit quality. The study concludes that strengthening QAR implementation can significantly enhance audit practices among independent CPAs. It recommends an improvement plan focusing on communication, tailored training, accessible resources, and continuous professional development to uphold high standards of audit quality.